2020
DOI: 10.1155/2020/6968595
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Mutations of Tim-3 Ligand and Exhausted Tim-3+ CD8+ T Cells and Survival in Diffuse Large B Cell Lymphoma

Abstract: Tim-3 is a promising target for antitumor immunotherapy. A number of clinical trials are evaluating the efficacy of anti-Tim-3 therapies as a single agent or combinations in solid tumors and haematologic malignancies. However, there remains a considerable lack of data on Tim-3 signalling, especially the genetic characteristics and immune microenvironment, in diffuse large B cell lymphoma (DLBCL). Herein, we identified three genetic mutations in galectin-9, a major ligand of Tim-3, in six patients with DLBCL (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Higher proportions of these cells were not significantly linked to cell-of-origin or genetic subtypes in DLBCL but instead associated with inferior survival in FL and DLBCL patients. These results are in line with previous studies that used TIM3 or LAG3 as surrogate markers to estimate Tcell exhaustion in DLBCL [51] or FL patients [52]. PD1 + TIM3 + T TOX cells were located within several spatial neighborhoods, thereby allowing for contact with various types of immune cells.…”
Section: Discussionsupporting
confidence: 91%
“…Higher proportions of these cells were not significantly linked to cell-of-origin or genetic subtypes in DLBCL but instead associated with inferior survival in FL and DLBCL patients. These results are in line with previous studies that used TIM3 or LAG3 as surrogate markers to estimate Tcell exhaustion in DLBCL [51] or FL patients [52]. PD1 + TIM3 + T TOX cells were located within several spatial neighborhoods, thereby allowing for contact with various types of immune cells.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, the suppression therapy of immune checkpoints has become a breakthrough point for refractory/relapsed malignant tumors. Some scholars have found that the combined inhibition of PD1/PD-L1, PD1/CTLA4, PD1/TIM-3, and PD1/LAG3 can significantly inhibit cytokines in response to malignant neoplasm therapy [5,[41][42][43][44]. T cell immunoglobulin and ITIM domain (TIGIT), as an inhibitory receptor, is an emerging cancer immunotherapy target.…”
Section: Discussionmentioning
confidence: 99%
“…The cognate ligand of TIM-3, Gal-9, is expressed by some lymphoma cells and MDSCs, where it serves to drive Th1 cell death and CTL immune exhaustion and, thus, impair antitumor T-cell responses [ 117 ]. Indeed, TIM-3 overexpression and exhaustion of TIM-3+ TILs have been shown to correlate with inferior outcomes in DLBCL [ 34 , 118 ]. The precise mechanisms by which TIM-3 expression on innate immune cells (i.e., NK cells, macrophages, and dendritic cells) contributes to immune dysfunction remain to be elucidated [ 116 ].…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…Moreover, TIM-3 and LAG-3 are nearly always expressed in the TME of cHL (>96% of cases) [ 213 ]. In both DLBCL and FL, expression of these ligands on TILs has been correlated with a decrease in treatment efficacy and overall survival [ 34 , 118 , 212 , 214 ]. Preclinical studies have shown enhanced cytotoxic and antitumor T-cell responses in the presence of anti-TIM-3 and anti-LAG-3 antibodies [ 34 , 215 ].…”
Section: Engaging the Antitumor Immune Responsementioning
confidence: 99%